2020
DOI: 10.3390/en13174333
|View full text |Cite
|
Sign up to set email alerts
|

Energetic, Economic and Environmental (3E) Assessment and Design of Solar-Powered HVAC Systems in Pakistan

Abstract: Rapid urbanization, global warming and enhanced quality of life have significantly increased the demand of indoor thermal comfort and air conditioning systems are not a luxury anymore, but a necessity. In order to fulfil this need, it is imperative to develop affordable and environmentally friendly cooling solutions for buildings. In this work, the 3E performance (energetic, economic and environmental) of electrically driven water-cooled vapour compression systems and thermally (solar) driven vapour absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…In view of the search for alternative energy sources and considering that there are polluting fuels in the atmosphere such as coal, heavy oil and tar; natural gas presents itself favorably [7]. When comparing natural gas with other biofuels, there is less CO2 emission.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the search for alternative energy sources and considering that there are polluting fuels in the atmosphere such as coal, heavy oil and tar; natural gas presents itself favorably [7]. When comparing natural gas with other biofuels, there is less CO2 emission.…”
Section: Resultsmentioning
confidence: 99%
“…Although the Brazilian matrix comes considerably from renewable sources, the socio-environmental impacts of some of these sources are considerable, when compared to other energy sources [5] The correlation between the evolution of energy demand and economic growth measured by GDP has been recurrent, and the increase in energy consumption can be attributed to air conditioning systems [6]. The demand for the expansion of the use of air conditioning and refrigeration systems can be perceived due to population growth, global warming, the increase in the social standard of living (increase in equipment inside buildings, lighting, increased demand for occupant comfort) and architectural characteristics, such as: the huge facades and the use of heat-absorbing surfaces [7,8]. In addition, it is known that around 30% of the energy demand of an enterprise is destined to air conditioning systems in different sectors (homes, schools, canteens, public offices, hospitals, markets, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Absorption chillers are a promising alternative, exhibiting considerable energysaving benefits, potential economic viability, and environmentally friendly features [16]. Given the search for alternative energy sources and considering that there are polluting fuels in the atmosphere, such as coal, heavy oil, and tar, natural gas presents itself favorably [7]. When comparing natural gas with other biofuels, there is less CO2 emission.…”
Section: Methodsmentioning
confidence: 99%
“…The correlation between the evolution of energy demand and economic growth measured by GDP has been recurrent, and the increase in energy consumption can be attributed to air conditioning systems [6]. The demand for the expansion in using air conditioning and refrigeration systems occurred due to population growth, global warming, the increase in the social standard of living, and architectural characteristics, among others [7,8]. In addition, air conditioning systems consume around 30% of an enterprise's energy demand in different sectors (homes, schools, canteens, public offices, hospitals, and markets) [9].…”
Section: Introductionmentioning
confidence: 99%
“…In this period, several configurations have been studied and analyzed in terms of stages, absorberrefrigerant pairs, drive medium, applications and cooling capacities. In the literature, studies of solar cooling thermal systems have been found with single-effect absorption machines and driven by various types of solar collectors: with nonconcentrating or stationary solar collectors [4,5,6,7,8,9,10,11,12,13,14,15,16], with parabolic cylinder collectors [6,14,17,18] and with linear Fresnel collectors [19]. Also, systems with absorption machines with two or more stages and with various types of solar collectors: with parabolic cylinder collectors [4,20] and with linear Fresnel collectors [21].…”
Section: Introductionmentioning
confidence: 99%